Implant Density and Curve Correction in Scoliosis Surgery using a Three-Dimensional-Based Correction Strategy - Bobby Kin-Wah Ng; Victor Illescas; Wai-Wang Chau (Journal of Orthopedics, Traumatology and Rehabilitation, 2022)
Introduction: The growing trend toward the use of pedicle screws for the operative treatment of patients with idiopathic scoliosis is to provide a three-dimensional (3D) deformity correction using a three-column fixation was observed. Reports have variable recommendations regarding the implant density as well as the configuration of the pedicle screws. This study re-evaluated implant density and curve correction currently based on the 3D correction strategy by comparing it to side-bending correction (SBC).